Hotel Reservation Management System - Koh, Wei Shun; Mohmad Hassim, Yana Mazwin (Applied Information Technology And Computer Science, 2021)
Hotel Time Johor Bahru is one of the hotel in Malaysia where located in Johor Bahru, Johor. The hotel currently uses BlogSpot blog for displaying hotel’s details only without having a proper reservation system and relied on third-party hotel reservation platform. The problems faced by the hotel currently are there will be fewer profits earned since the hotel needs to pay the commission to the external booking portal each time a guest made a reservation from the respective booking portal. Besides, the hotel looks less impressive without having its own booking engine since some guests prefer the hotel’s own booking system for reserving a room instead of using an external booking portal. The objectives of this project is to design a hotel reservation management system and then to develop a hotel reservation management system for Hotel Time Johor Bahru. In this project, the Waterfall model is applied to assist the project development. The system is a web-based system developed based on Structured approach. There are four programming language used to develop the system namely HTML, CSS, PHP, Javascript and the database used is MySql. The hotel reservation management system will automate the major operations of the hotel in areas of booking, accommodation, account details, inventory, reporting, housekeeping and provide online reservation for guests. Testing result shows that all the functions in the system are outputting as expected result. The system will improve the staffs’ and customers’ efficiency especially for those who are involved in record keeping, searching of customer’s information and account details of customer’s booking.